PEMETAAN KESESUAIAN IKLIM TANAMAN PAKAN SERTA KERENTANANNYA TERHADAP PERUBAHAN IKLIM DENGAN SISTEM INFORMASI GEOGRAFI (SIG) DI PROVINSI BALI - Abd. Rahman As-syakur; I Wayan Suarna; I Wayan Rusna; I Nyoman Dibia (Pastura : Jurnal Ilmu Tumbuhan Pakan Ternak)
Forage is one of the supporting factors in planning animal production. Climate condition is one factor which influence forage production. This research attempted to map the class suitability of climate for seven forage species in Bali province and to analysis the level of vulnerability toward climate changes by using Geography Information System (GIS). The results showed that four from seven species observed have class suitability with climate S1. Rain climate factor was the important factor which was influence the climate unsuitability of forage in Bali province. The effect of climate change, such as La Nina 1998 caused positive and negative impacts towards the distribution of class suitability of climate at that year. The incident of La Nina caused the reduction of area of class suitability of S1, S2, and N climate, meanwhile increase the area of class suitability of S3 climate. On the other hand, some location of climate suitability class also changed due to climate change.